SIRI' NA PACCE CULTURE IN RETAILER BASED ON ISLAMIC PERSPECTIVE BUSINESS ETHICS - Misbach, Irwan (Jurnal Adabiyah, 2020)
The purpose of this study was to determine the culture of siri' na pacce in revealing the profits of retail traders from the perspective of Islamic business ethics. This type of research is a qualitative descriptive study with an ethnographic approach. This study obtained data from retailers of Bugis-Makassar ethnicity and Muslim who trade at the Panakukkang Market in Makassar. Data collected through a series of observation methods, interviews, secondary data from literature books, journals, the internet, and other complementary data. Research results internalization of siri' na pacce culture and Islamic business ethics in trading produce material and non-material benefits. The internalization of siri' na pacce culture with Islamic business ethics results in the values of tongeng and the principle of truth, the value of lempu' and the principle of tauhid, balance, ihsan, and the value of adele' and the focus of truth. The values in the siri' na pacce culture can implement Islamic business ethics in trade to achieve world happiness and the end, which is the goal of human life.الغرض من هذه الدراسة هو تحديد ثقافة السيري في الكشف عن أرباح تجار التجزئة من منظور أخلاقيات العمل الإسلامية. هذا النوع من البحث هو دراسة وصفية نوعية ذات نهج إثنوغرافي. تم الحصول على مصادر البيانات من تجار التجزئة من عرقية Bugis-Makassar والمسلمين الذين يتاجرون في سوق Panakukkang في Makassar. تم جمع البيانات من خلال سلسلة من طرق المراقبة والمقابلات والبيانات الثانوية من كتب الأدب والمجلات والإنترنت والبيانات التكميلية الأخرى. نتائج البحث عن استيعاب ثقافة السيري وأخلاقيات العمل الإسلامية في التجارة تنتج فوائد مادية وغير مادية. إن استيعاب ثقافة سيري مع أخلاقيات العمل الإسلامية ينتج عنه قيم توغنغ ومبادئ الحقيقة ، وقيم ليمبو ومبادئ التوحيد ، والتوازن ، والحقيقة ، وقيم الإحسان ، وأديل ومبادئ الحقيقة. يمكن تطبيق القيم الواردة في ثقافة السيري ومبادئ أخلاقيات العمل الإسلامية في التجارة لتحقيق السعادة العالمية والغاية التي هي هدف حياة الإنسان على هذه الأرض.Tujuan penelitian ini untuk mengetahui budaya siri’ na pacce dalam mengungkap keuntungan usaha pedagang eceran perspektif etika bisnis Islam. Jenis penelitian ini adalah penelitian deskriptif kualitatif dengan pendekatan etnografi. Sumber data diperoleh dari pedagang eceran bersuku Bugis-Makassar dan beragama Islam yang berdagang di Pasar Panakukkang Makassar. Data yang dikumpulkan melalui serangkaian metode observasi, wawancara, data sekunder dari literatur buku, jurnal, internet, dan data pelengkap lainnya. Hasil Penelitian internalisasi budaya siri’ na pacce dan etika bisnis Islam dalam berdagang menghasilkan keuntungan materi dan non materi. Internalisasi budaya siri’ na pacce dengan etika bisnis Islam menghasilkan nilai togeng dan prinsip kebenaran, nilai lempu’ dan prinsip tauhid, keseimbangan, kebenaran, ihsan, dan nilai adele’ dan prinsip kebenaran. Nilai-nilai terdapat di budaya siri’ na pacce dan prinsip-prinsip etika bisnis Islam dapat di implementasikan dalam berdagang untuk mencapai kebahagian dunia dan akhir yang menjadi tujuan hidup manusia di muka bumi ini.